The Effect of Kahoot-Based Assessment on Students’ Interest in Qur’an and Hadith Learning at MAN 1 Gresik - Aqila Zahra Rohmah; Abdul Basir (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aimed to examine changes in students’ interest in learning assessment activities following the implementation of Kahoot-based assessment in the Qur’an and Hadith subject among 10th-grade students at MAN 1 Gresik. Methods – This study employed a quantitative pre-experimental design with a one-group pretest-posttest design, conducted with 33 students from the 10th-grade class 6 at MAN 1 Gresik, selected through total sampling. Data were collected using a 25-item Likert-scale questionnaire measuring students’ interest in learning assessment activities. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample t-test. Findings – The mean interest score increased from 68.81 in the pretest to 76.09 in the posttest. The paired-sample t-test showed a statistically significant difference between the two measurements (p = 0.000 < 0.05). The calculated effect size was large (Cohen’s d = 0.87), indicating a substantial increase in students’ reported interest following participation in the Kahoot-based assessment activity.Research Implications – This study suggests that Kahoot may support a more interactive and engaging assessment experience and may be associated with higher levels of student interest in learning assessment activities. However, the results should be interpreted with caution due to the use of a single-group design and a relatively small sample. Further studies involving control groups, larger samples, and longer intervention periods are recommended.